2019
DOI: 10.1016/j.redox.2019.101140
|View full text |Cite
|
Sign up to set email alerts
|

miR-125b suppresses oral oncogenicity by targeting the anti-oxidative gene PRXL2A

Abstract: Oral squamous cell carcinoma (OSCC) is a globally prevalent malignancy. The molecular mechanisms of this cancer are not well understood and acquire elucidation. Peroxiredoxin like 2A (PRXL2A) has been reported to be an antioxidant protein that protects cells from oxidative stress. Our previous study identified an association between PRXL2A upregulation in OSCC and a worse patient prognosis. MicroRNAs (miRNAs) are small non-coding RNAs that are involved in the modulation of biological/pathological properties. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 57 publications
(87 reference statements)
0
41
0
1
Order By: Relevance
“…Abundant evidence had verified that miRNAs construct a complex network of genic expression and biologic pathway regulation, which has the function of prognosis and treatment target in many kinds of cancers . So far, several studies had proofed certain miRNAs with prognostic roles, such as miR‐654‐5p, miR‐125b, microRNA‐194‐5p, miR‐196b, miR‐548b, and so on. Nevertheless, the majority of formerly researches have concentrated on unimolecular incidents, limited cases, nonstandardized detective technique, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant evidence had verified that miRNAs construct a complex network of genic expression and biologic pathway regulation, which has the function of prognosis and treatment target in many kinds of cancers . So far, several studies had proofed certain miRNAs with prognostic roles, such as miR‐654‐5p, miR‐125b, microRNA‐194‐5p, miR‐196b, miR‐548b, and so on. Nevertheless, the majority of formerly researches have concentrated on unimolecular incidents, limited cases, nonstandardized detective technique, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis followed protocols that we previously established using various primary antibodies (Table S4) and a range of secondary antibodies (Table S5) (4,9). GAPDH was used as the internal control for Western blotting.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…When develop new strategies that block HNSCC development, a molecular understanding of HNSCC pathogenesis is important (1). Over the last decade, many studies have indicated that miRNAs and theirs targeted genes are highly associated with OSCC promotion and progression (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…It had reported that miR-125b-2-3p was down-regulated in hepatocellular carcinoma [25] and small cell osteosarcoma [26] but upregulated in tumor stroma of colon cancer [27] . In OSCC, although miR-125b was found to inhibit the progression of OSCC [28] , the function of miR-125b-2-3p is still uncertain. In our study, we con rmed that the expression levels of miR-125b-2-3p were negatively correlated with TNM classi cation and lymph node metastasis in OSCC patients.…”
Section: Discussionmentioning
confidence: 99%